Атака по правилам - Панов Вадим Юрьевич (Тайный город. Коллекция, 2012)
Экземпляры: ф.20 (2012) / Инвентарный номер: 54477 / Цена: / Сис.шифр: 84(2Рос=Рус)6-4 / Авт.знак: П 16 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=Рус)6-445